1992
DOI: 10.1007/bf01811468
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of cultures of catheter-drawn blood and heparin-lock fluid to diagnose infection in hematologic patients

Abstract: The results of bacteriologic cultures of blood and heparin-lock fluid, both drawn from the central venous catheters of 54 consecutive oncohematologic patients, have been used to determine their value for the diagnosis of systemic and catheter-associated infection. In 30 patients with clinical signs of infection (bacteremia or septicemia), 74 of 1000 (7.4%) heparin-lock fluid cultures, 114 of 542 (21%) catheter-drawn blood cultures, and 36 of 134 (26%) venipuncture blood cultures became positive, whereas in 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…All patients were treated according to a local protocol to prevent infections with aerobic Gram-negative rods, Viridans streptococci and Candida spp. 9 Prophylactic treatment included neomycin (250 mg), polymyxin B (1.10 6 U) orally qd, pipemidic acid 400 mg orally bid, and amphotericin B 200/10 mg qd. After 10 days of treatment, the dosage of the regime was reduced (half of the dosage in mg), except for the pipemidic acid.…”
Section: Patients and Study Designmentioning
confidence: 99%
“…All patients were treated according to a local protocol to prevent infections with aerobic Gram-negative rods, Viridans streptococci and Candida spp. 9 Prophylactic treatment included neomycin (250 mg), polymyxin B (1.10 6 U) orally qd, pipemidic acid 400 mg orally bid, and amphotericin B 200/10 mg qd. After 10 days of treatment, the dosage of the regime was reduced (half of the dosage in mg), except for the pipemidic acid.…”
Section: Patients and Study Designmentioning
confidence: 99%
“…15 Few studies have examined the usefulness of endoluminal surveillance culture (SC) to prevent CRBSI. 16,17 Heparin solution is commonly used to lock the catheter to prevent thrombosis, and there is some controversy over whether or not to include heparin in blood culture samples. Previous studies have shown no interference of heparin with the growth of microorganisms 18,19 and the usefulness of the blood-heparin mixture culture to predict CRBSI.…”
mentioning
confidence: 99%